Prevalence of diarrhoeal pathogens among children under five years of age with and without diarrhoea in Guinea-Bissau. - Sointu Mero (Public Library of Science (PLoS), 2021)
Background Childhood diarrhoea, a major cause of morbidity and mortality in low-income regions, remains scarcely studied in many countries, such as Guinea-Bissau. Stool sample drying enables later qPCR analyses of pathogens without concern about electricity shortages. Methods Dried stool samples of children under five years treated at the Bandim Health Centre in Bissau, Guinea-Bissau were screened by qPCR for nine enteric bacteria, five viruses, and four parasites. The findings of children having and not having diarrhoea were compared in age groups 0-11 and 12-59 months. Results Of the 429 children- 228 with and 201 without diarrhoea- 96.9% and 93.5% had bacterial, 62.7% and 44.3% viral, and 52.6% and 48.3% parasitic pathogen findings, respectively. Enteroaggregarive Escherichia coli (EAEC; 60.5% versus 66.7%), enteropathogenic E. coli (EPEC; 61.4% versus 62.7%), Campylobacter (53.2% versus 51.8%), and enterotoxigenic E. coli (ETEC; 54.4% versus 44.3%) were the most common bacterial pathogens. Diarrhoea was associated with enteroinvasive E. coli (EIEC)/Shigella (63.3%), ETEC (54.4%), astrovirus (75.0%), norovirus GII (72.6%) and Cryptosporidium (71.2%). The only pathogen associated with severe diarrhoea was EIEC/Shigella (p<0.001). EAEC was found more frequent among the infants, and EIEC/Shigella, Giardia duodenalis and Dientamoeba fragilis among the older children. Conclusions Stool pathogens proved common among all the children regardless of them having diarrhoea or not.